The drama of Ibsen and Strindberg - Lucas, F. L. (New York : Macmillan, 1962)
The plays of both Scandinavian dramatists are analyzed. A final chapter contrasts their personalities and work.
Keywords: Ibsen, Henrik. -- 1828-1906.; Strindberg, August, -- 1849-1912.